The Franklin Search in 1850 - Woodward, F. J. (Polar Record, 1950)
We ought, in 1950, to be celebrating the centenary of the end of the Franklin Search: so great was the opportunity which one of the 1850 expeditions narrowly missed. As it is, we have nine years left to wait for that celebration; and a hundred years ago there were nine years left in which men were called upon to risk and sometimes to give their lives in the quest for the missing expedition, and in which the relatives of its members were kept in suspense, hope gradually dulling into resignation. The year. 1850 has instead the lesser distinction of being the first year in which traces of the Franklin Expedition were discovered.